Anthropological Description of Skeletal Material from the Dniester Barrowcemetery Complex, Yampil Region, Vinnitsa Oblast (Ukraine) - Litvinova, Liudmyla V.; Łukasik, Sylwia; Żurkiewicz, Danuta; Gwizdała, Marta; Chyleński, Maciej; Malmström, Helena; Jakobsson, Mattias; Juras, Anna (Baltic-Pontic Studies, 2017)
Anthropological examinations were performed on skeletal material from four barrow necropolises located in the Yampil Region (Ukraine) and dated to the Eneolithic, Bronze Age and Iron Age. The purpose of the examinations was the determination of sex and age at death of individuals, reconstruction of their stature and assessment of their status of health. The examinations covered 61 individuals: 17 children and 44 adults. Their health status was assessed using four common indicators: linear enamel hypoplasia, cribra orbitalia, porotic hyperostosis and dental caries.